2016
DOI: 10.1152/ajprenal.00273.2016
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cytokine signaling in salt-sensitive hypertension

Abstract: Activated immune cell populations contribute to hypertension in part through inciting damage to the kidney and by provoking inappropriate sodium reabsorption in the nephron. Inflammatory mediators called cytokines produced by T lymphocytes and macrophages act on specific sodium transporters in the kidney, augmenting their activity or expression, with consequent expansion of intravascular fluid volume and cardiac output. The overlapping functions of these cytokines, each of which may activate multiple receptors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Dietary salt is thought to be a major cause of increased blood pressure 41 . Insulin resistance and consequent hyperinsulinemia 40 as well as proinflammatory cytokines 42 also play important roles in obesity-related hypertension. Whereas obesity and essential hypertension are both characterized by sympathetic overactivity, certain features of such altered activity in human obesity and obesity-related hypertension differ from those in essential hypertension 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Dietary salt is thought to be a major cause of increased blood pressure 41 . Insulin resistance and consequent hyperinsulinemia 40 as well as proinflammatory cytokines 42 also play important roles in obesity-related hypertension. Whereas obesity and essential hypertension are both characterized by sympathetic overactivity, certain features of such altered activity in human obesity and obesity-related hypertension differ from those in essential hypertension 43 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, as depicted in TABLE 2, DOCA-salt hypertension is unmodified by TNF-␣, IL-6, or IL-17 deficiency which is in contrast to the amelioration observed in of angiotensin II-induced hypertension. Finally, cytokines have frequently overlapping functions, which presents a challenge in studies that target individual cytokines to evaluate their role in hypertension and tissue injury(39). All these circumstances are responsible for the variability in the amelioration of hypertension attributed to suppression of specific cytokines.…”
mentioning
confidence: 99%
“…This protection may be caused by a dual mechanism: reduced inflammatory flow and reduced TGF-β signaling pathway. Recent studies have shown that immune system cells are involved in the pathogenesis of hypertension through their role in the kidney, blood vessels, and brain, so immune regulation may be a new approach to reduce blood pressure and to limit hypertension-induced organ damage ( Schreiner and Kohan, 1990 ; Crowley et al, 2011 ; Crowley and Jeffs, 2016 ). Transforming growth factor-β (TGF-β) is a key driver of renal fibrosis, especially when activating the renin–Ang system (RAS), which is the main cause of hypertension ( Kagami et al, 1994 ; Wei et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%